Characteristics of Household Waste Management in an Effort to the Achievement of Sustainable Development Goals (SDGs) in Krembangan District of Surabaya City - Abdul Wahid Arfanto; F Rooslan Edy Santosa (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Sustainable Development Goals (SDGs) is a continuous development program which 17 destinations.This research was conducted in District Krembangan Surabaya, the goal is to determine the level of knowledge, attitudes and behavior of public in waste management activities and the role of government in waste management activities. The determination of the respondents were selected by a procedure in the Study of Environmental Health Risk Assessment (EHRA). The data obtained from interviews and observations will be entered into the software EHRA, then processed using Microsoft Excel. The results of this study include the management of household waste, the frequency and accuracy of transporting waste and waste sorting activities. 89% of respondents are already carrying out waste management by means of collected and discharged intotemporary landfill. Waste hauling was done in a regular frequency, as much as 14% respoden have done sorting waste at home before being dumped intotemporary landfill.